2017
DOI: 10.3892/ol.2017.7425
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin‑mediated regulation of the cell cycle and DNA damage response exerts antitumor activity in human hepatocellular carcinoma

Abstract: A novel module-search algorithm method was used to screen for potential signatures and investigate the molecular mechanisms of inhibiting hepatocellular carcinoma (HCC) growth following treatment with silymarin (SM). The modules algorithm was used to identify the modules via three major steps: i) Seed gene selection; ii) module search by seed expansion and entropy minimization; and iii) module refinement. The statistical significance of modules was computed to select the differential modules (DMs), followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…17 Recently, it was found that it has an antitumor activity in HCC. 18 To the extent of our knowledge, no studies investigated the effect of NSEE, TQ, or silymarin on EGFR/ERK1/2 signaling pathway in DENA-induced HCC in rats. Consequently, we designed our study to focus on the chemopreventive effect of NSEE, TQ, or silymarin as a hepatoprotective agent on the EGFR/ERK1/2 signaling in the precancerous stage of HCC in rats induced by DENA and CCl 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Recently, it was found that it has an antitumor activity in HCC. 18 To the extent of our knowledge, no studies investigated the effect of NSEE, TQ, or silymarin on EGFR/ERK1/2 signaling pathway in DENA-induced HCC in rats. Consequently, we designed our study to focus on the chemopreventive effect of NSEE, TQ, or silymarin as a hepatoprotective agent on the EGFR/ERK1/2 signaling in the precancerous stage of HCC in rats induced by DENA and CCl 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Silymarin is nontoxic to humans and has been employed as a protective treatment in acute and chronic liver diseases . Recently, it was found that it has an antitumor activity in HCC . To the extent of our knowledge, no studies investigated the effect of NSEE, TQ, or silymarin on EGFR/ERK1/2 signaling pathway in DENA‐induced HCC in rats.…”
Section: Introductionmentioning
confidence: 99%
“…This discovery contributes to the evolving understanding of NUSAP1's role as a pivotal mediator of CAF activation, linking extracellular cues like lactate to intracellular signaling pathways. This may also elucidate the multifaceted functions of NUSAP1 in cellular processes beyond mitosis [ 70 , 71 ]. Importantly, the upregulation of DESMIN-positive CAFs, induced by lactate treatment and NUSAP1-mediated mechanisms, reveals intriguing functional consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Looking towards bioactive compounds derived from plants that target IL-6 in HCC, including Curcuma phaeocaulis [135], Curcuma aromatica, Polygonum cuspidatum [136], and Silybum marianum [137], it has been shown that curcumin inhibits IL-6-induced JAK/STAT3 signaling cascades through negative feedback, suppressing the development of inflammation in HCC [135]. Even though their molecular mechanism is not fully understood, both silymarin and resveratrol are also used as alternative treatments for their anti-HCCassociated effects, possibly through the induction of cell cycle arrest [137] and the installation of apoptotic cell death [136].…”
Section: Il-6 Targetsmentioning
confidence: 99%